Paneer Whey-Apricot Wine: Effect of bentonite treatment and aging and comparative sensory evaluation - Jindal, Harsh; Panjagari, Narender Raju; Ganguly, Sangita (Indian Journal of Dairy Science, 2026)
This study explored the impact of varying bentonite concentrations and aging on the physico-chemical properties and comparative sensory analysis of paneer whey-apricot wine (PWAW) with whey wine (WW), apricot wine (AW) and a commercial apricot wine (MAW). Wine namely WW (without apricot) and AW (without whey) were considered as control samples. The results revealed that the light transmittance of PWAW treated with 1% bentonite was significantly higher (89.75%) compared to the untreated samples (80.81%) (p<0.05). However, increasing concentration of bentonite resulted in significant reduction in total solids, total soluble solids, total and reducing sugars (p<0.05). Bentonite at 0.2% did not have any significant effect on the ethanol content (p<0.05). Also, its use at 0.5% and above did not have any significant effect on the lightness value (L*) of PWAW samples (p>0.05). Aging resulted in slight but significant decrease in total soluble solids, total phenolics, ethanol and DPPH activity (p<0.05). However, the L* was found to significantly increase from 75.89 to 77.01 at the end of 30 days of aging (p<0.05). Comparison of different wines revealed that the L*value of WW (98.80), AW (78.88), PWAW (75.89), and MAW (70.43) were found to be in decreasing order. Further, PWAW was found to have significantly high amount of total phenolics, ABTS and DPPH activity levels compared to MAW, AW, and WW (p<0.05). Sensory evaluation revealed that the overall score of PWAW was significantly higher compared to AW and WW (p<0.05). Particularly, aroma and bouquet, acetic acid (vinegary), total acidity, flavour, and general quality scores of PWAW samples were found to be significantly higher compared to AW and WW samples (P<0.05). This study revealed the role of bentonite treatment (0.5%) in providing better clarity to PWAW. Also, the study highlighted the superior antioxidant activity and sensory scores of PWAW compared to AW, WW and MAW samples.